Towards a Socialist Reform in the Greek Educational System? (a situational approach) - Bombas, Leonidas C. (Études helléniques / Hellenic Studies, 1983)
An historical account of the major reforms attempted in the Greek educational system over the last seventy years shows that stability has characterized the system since its establishment in 1830. Reforms have been either strongly opposed or interrupted by the conservative and reactionary forces that have almost exclusively governed Greece. A few liberal measures introduced into the system had never had the chance to “flourish into full-fledged” progressive reforms. The so-called ”PASOK phenomenon” which successfully managed to put together all anticonservative forces of Greek society and capitalized on their true thirst for Allaghi (Change) in the 1981 general elections, has promised to radically alter the philosophy and the structure of the Greek educational system. The factors, however, contributing to the stability of the system and, more so, the stagnant economy, do not leave much room for such substantial changes despite the many theories of the PASOK people and its “charismatic” leader A. Papandreou. As long as the social and economic apparatus of Greek society remains basically unchanged, major and socialist-like reforms in education will not be materialized. More than a full year of PASOK government has definitely been a better but far from socialist administration on both the internal and external fronts. The few minor changes introduced into the Greek society do not seem, so far, to challenge the longstanding tradition of stability. Education stands as an illustration of that continuing tradition.